A Case Study of the Your Educational Path Digital Education Ecosystem in Crisis Contexts: AI, Mental Health, and Equity in Ukraine - Koshevets, Oleksii (International Review of Research in Open and Distributed Learning, 2026)
This study investigated the development and implementation of the YEP (Your Educational Path) system, an educational technology ecosystem, developed by Tatl Technology, and deployed across Ukraine during the COVID-19 pandemic and ongoing war. Using a qualitative case study approach, this research drew on official government data from a learning management system pilot program (2019–2023), usage analytics (2019–2024), and documentation from public-private stakeholders. The analysis evaluates the YEP ecosystem through four dimensions: functionality, scalability, policy alignment, and crisis resilience. Key findings included rapid adoption across 2,193 schools, engagement of over 1.8 million users, and integration of AI-driven diagnostics and mental health support tools by the end of 2023. These findings have contributed to global discourse on education in emergencies and suggested a replicable model for resilient digital schooling in conflict-affected contexts.